Konflik Batin dalam Novel Moga Bunda Disayang Allah Karya Tere Liye - Afrianti, Nelly; Abdurahman, Abdurahman; Nursaid, Nursaid (Universitas Negeri Padang, 2012)
The purpose of this study was (1) to describe the form of inner conflict of main character in the novel Moga Bunda Disayang Allah by Tere Liye from the psychology of literature based on ego defense mechanism proposed by Ferdinand Zaviera, and (2) to describe the cause of inner conflict of main character in the novel Moga Bunda Disayang Allah by Tere Liye examined from the psychology literature. In this data of this research are forms and causes of inner conflict of main character in novel Moga Bunda Disayang Allah by Tere Liye. Sources of this research data was a text that describing inner conflict of the main character from novel Moga Bunda Disayang Allah by Tere Liye published by Republika Puslisher, 11th prints 11 November 2011 in Jakarta.